SISTEM KENDALI PROTOTYPE KERETA MAGLEV UNTUK MENGATUR PERGERAKAN MENGGUNAKAN NODEMCU ESP8266 (Politeknik Perkeretaapian Indonesia Madiun, 2022)
Maglev is the basis of fast train technology by lifting an object to a reference using a magnetic field. This system is used to reduce the friction force generated by a component that makes direct contact. This paper studies maglev train systems in the framework of the development of control system technology on fast trains. The maglev train control system was prototyped and tested in terms of moving forward on the straight path, mounting and system performance. The maglev train prototype's prototype movement control method is to set the magnetic tensile and thrust forces of the two magnetic poles on the means and trajectories using operator commands via smartphone using Blynk software. In this case the hall effect sensor is applied to detect the condition of the magnetic pole on the trajectory which is then used to determine the change in the artificial magnetic pole that is in the means. Test results from the maglev prototype drove at an average speed of 0.204 m/s